Impact of sequential therapy with osimertinib on the overall survival in patients with EGFR-mutant non-small cell lung cancer - Minehiko Inomata; Masahiro Matsumoto; Isami Mizushima; Kana Hayashi; Zenta Seto; Kotaro Tokui; Chihiro Taka; Seisuke Okazawa; Kenta Kambara; Shingo Imanishi; Toshiro Miwa; Ryuji Hayashi; et al. (The Egyptian Journal of Bronchology, 2022)
Abstract Purpose We conducted a retrospective analysis of the data of patients with epidermal growth factor receptor (EGFR)-mutant non-small cell lung cancer (NSCLC) to investigate the associations between clinical factors and the overall survival. Methods We retrieved the patient data from the medical charts. Patients who were diagnosed as having EGFR-mutant NSCLC and treated with EGFR-tyrosine kinase inhibitors (EGFR-TKIs) between 2007 and 2020 at our institution were included in the analysis. Results A total of 130 patients were included in the analysis. A log-rank test identified EGFR exon 19 deletion in the tumor, an Eastern Cooperative Oncology Group performance status of 0–1, serum lactate dehydrogenase level, local therapy for brain metastasis, and sequential osimertinib therapy for patients with the T790M mutation acquired after primary EGFR-TKI therapy as being significantly associated with a better overall survival. Analysis using a Cox proportional hazards model identified EGFR exon 19 deletion in the tumor, an Eastern Cooperative Oncology Group performance status of 0–1, serum lactate dehydrogenase level, local therapy for brain metastasis, and sequential therapy with osimertinib as being independently associated with a prolonged overall survival. Conclusion Our analysis suggested that EGFR mutation status, an Eastern Cooperative Oncology Group performance status, serum lactate dehydrogenase level, local therapy for brain metastasis, and sequential therapy with osimertinib were associated with overall survival in patients with EGFR-mutant NSCLC in clinical practice settings.